Early ontogeny of the African bony-tongue (Heterotis niloticus) and the effect of Artemia and rotifer live feeds on larval digestive enzyme activity and performance - Ofori-Darkwah, Prince; Adjei-Boateng, Daniel; Edziyie, Regina Esi; Agbo, Nelson Winston; Lund, Ivar (Frontiers in Aquaculture, 2024)
High larval and fry mortality has been a major challenge to the commercial culture of the African bony-tongue (Heterotis niloticus). Research indicates inadequate feeding to be a possible cause of the high mortality rates of larvae/fry grown in captivity. An experiment was conducted to first describe the developmental stages of H. niloticus eggs and larvae until schooling, 6 days after hatching (DAH), at 26°C. The morphological development, survival, growth (weight gain and length), and swimming behavior of the larvae were monitored. A follow-up feeding trial was conducted with H. niloticus fry from 6 to 27 DAH involving four treatments: feeding with Artemia nauplii; a combined feed of 50% Artemia nauplii and 50% rotifers (w/w); feeding with rotifers; and no feeding. The activities of three digestive enzymes (trypsin, lipase, and amylase) were assessed in fry exposed to the live feed treatments. At hatching, the larvae had a large, vascularized yolk sac filled with yolk platelets, which occupied approximately one-third of the total body length of the abdominal cavity. Yolk platelet reabsorption started at 1 DAH and was complete at 6 DAH. Metamorphosis was completed at 6 DAH, and schooling behavior was observed. For the feeding trial, the fry that received Artemia nauplii underwent the fastest development until 27 DAH. Similarly, the survival rate was considerably higher in fry fed with Artemia nauplii than in those that received a combination of Artemia nauplii and rotifers or only rotifers. Overall, the survival rates for fry fed with Artemia nauplii and larvae co-fed were 72.7% ± 0.9% and 41.2% ± 3.3%, respectively. Fry did not survive until 27 DAH in the rotifer-fed and unfed treatment groups. Digestive enzyme activity differed significantly (p< 0.05) between treatments and sampling dates. All digestive enzymes were detectable at the onset of mouth opening (5 DAH) and fluctuated through the 7 and 9 DAH. Lower enzyme activity was observed when the fry were subjected to starvation or the rotifer treatment. Results indicate that Artemia nauplii is the best live feed organism for H. niloticus larviculture.